2008
DOI: 10.1165/rcmb.2007-0036oc
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide Corrects Newly Found Ceramide Deficiency in Cystic Fibrosis

Abstract: Chronic and persistent lung infections cause the majority of morbidity and mortality in patients with cystic fibrosis (CF). Galactosyl ceramide has been previously shown to be involved in Pseudomonas internalization. Therefore, we assessed ceramide levels in the plasma of patients with CF and compared them to healthy volunteers using high-performance liquid chromatography followed by mass spectrometry. Our results demonstrate that patients with CF display significantly lower levels of several ceramide sphingol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
93
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 34 publications
4
93
3
1
Order By: Relevance
“…Global gene expression and proteomic analyses have not identified a distinct pathway but revealed that defective CFTR results in upregulation of genes and proteins involved in protein ubiquitination, mitochondrial oxidoreductase activity, and lipid metabolism and implicated defects in the NFkB, lipid, and HSP70 systems (6)(7)(8). More recently, defective CFTR has been associated with altered sphingolipid patterns and metabolism (9)(10)(11)(12).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Global gene expression and proteomic analyses have not identified a distinct pathway but revealed that defective CFTR results in upregulation of genes and proteins involved in protein ubiquitination, mitochondrial oxidoreductase activity, and lipid metabolism and implicated defects in the NFkB, lipid, and HSP70 systems (6)(7)(8). More recently, defective CFTR has been associated with altered sphingolipid patterns and metabolism (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Two different groups recently investigated ceramide mass in different CF mouse models, yet came to opposite conclusions whether absence of wild-type CFTR increases or decreases ceramide mass (11,12). The group that found significantly increased plasma and tissue ceramide levels in mice older than 16 weeks had investigated several different CFTR 2/2 mouse models (12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility has been raised that interfering with sphingolipids could be of therapeutic relevance in CF patients [6]. Indeed, fenretinide (4-hydroxy phenylretinamide) is a synthetic retinoid derivative, related to vitamin A. Fenretinide has been investigated for potential use in the treatment of cancer, rheumatoid arthritis, acne, psoriasis, and CF [7]. In an earlier study, Mcilroy et al showed that fenretinide-mediated retinoic acid receptor signaling and inhibition of ceramide biosynthesis regulates adipogenesis, lipid accumulation, mitochondrial function, and nutrient stress signaling in adipocytes and adipose tissue.…”
mentioning
confidence: 99%